Parentalidade e conjugalidade na adolescência : uma proposta interventiva - Maia, Joviane Marcondelli Dias (2010)
Adolescent pregnancy rate in Brazil is a public health problem. In general, research in the area of adolescent parenthood, and official data, are directed to motherhood in this phase with descriptive studies. Marital relationship in adolescence is a largely neglected theme, with lack of intervention research. Thus, the importance of the present study due to the lack of research in the area, the risks involved in adolescent pregnancy for the couple of teen parents and for child development, and the need to develop public policies. This research involved two studies. Study 1 was aimed at developing, implementing and evaluating the effectiveness of an intervention program for young couples, when at least one couple member had their first child during adolescence, and whose firstborn were less than seven years of age. The intervention seeked to improve marital and parental skills. Study 2 was aimed at replicating the intervention program for parents in Study 1, and evaluating it with adolescents parents whose children were in early infancy. Participants were referred by institutions of Sao José do Rio Preto area, São Paulo estate. Two couples of parents participated in the Study 1 and at least one had been an adolescent parent, with ages ranging from 24 - 30 years. In study 2, two couples of parents aged between 15 - 18 years participated. Schooling in the two studies ranged from incomplete Elementary School to incomplete High School. All participants had dropped out of school. Multiple measures were taken, with some instruments applied in three moments (pretest, posttest and follow-up), and records of self-reporting during the interventional procedure. In Study 1 the instruments and types of data collection used were: Parent Interview, Brazil Economic Classification Criterion, Marital Social Skills Inventory, Parental Styles Inventory, The Child Abuse Potential Inventory, Daily Record of Parental Satisfaction, Daily Record of Marital Satisfaction, A Field Diary, Final Interview and Followup Interview; and in Study 2: Parent Interview, Daily Record of Parental Satisfaction, Daily Record of Marital Satisfaction, Diary of Field, Final Interview and Follow-up Interview. Interventions were performed in the house of participants, lasting approximately three months with each couple. The intervention consisted primarily of interactive games directed to relevant skills training and instructions on the main themes of the study. The procedures was responsible for maximizing engagement and participation of couples. Results of the studies showed the effectiveness of intervention terms of improving parenting and marital skills expressed with an increase of scores of the instruments, as well as with their statements during the interventional procedure. Analysis of the satisfaction of participants in daily marital and parental roles indicated in several cases, a mutual influence between structures of autocorrelation and cross correlation parental and marital subsystems, at the beginning and end of the study, indicating could changes, tending to independent responses. It is hoped that this research contributes to the appropriateness of intervention programs that address parenting and marital relationship in adolescence, to stimulate significant protective factors and the resilience process. Prevention could occurs at various levels, including parents who had their children in adolescence and their children. Due to the fact that they are no longer adolescents, it does not mean they should be free from adolescent parenthood risks. Such issues should be reviewed by professionals of the area with development of public policies.